Staphylococcus aureus Tissue Infection During Sepsis Is Supported by Differential Use of Bacterial or Host-Derived Lipoic Acid. - Azul Zorzoli; James P Grayczyk; Francis Alonzo (PLoS Pathogens)
To thrive in diverse environments, bacteria must shift their metabolic output in response to nutrient bioavailability. In many bacterial species, such changes in metabolic flux depend upon lipoic acid, a cofactor required for the activity of enzyme complexes involved in glycolysis, the citric acid cycle, glycine catabolism, and branched chain fatty acid biosynthesis. The requirement of lipoic acid for metabolic enzyme activity necessitates that bacteria synthesize the cofactor and/or scavenge it from environmental sources. Although use of lipoic acid is a conserved phenomenon, the mechanisms behind its biosynthesis and salvage can differ considerably between bacterial species. Furthermore, low levels of circulating free lipoic acid in mammals underscore the importance of lipoic acid acquisition for pathogenic microbes during infection. In this study, we used a genetic approach to characterize the mechanisms of lipoic acid biosynthesis and salvage in the bacterial pathogen Staphylococcus aureus and evaluated the requirements for both pathways during murine sepsis. We determined that S. aureus lipoic acid biosynthesis and salvage genes exist in an arrangement that directly links redox stress response and acetate biosynthesis genes. In addition, we found that lipoic acid salvage is dictated by two ligases that facilitate growth and lipoylation in distinct environmental conditions in vitro, but that are fully compensatory for survival in vivo. Upon infection of mice, we found that de novo biosynthesis or salvage promotes S. aureus survival in a manner that depends upon the infectious site. In addition, when both lipoic acid biosynthesis and salvage are blocked S. aureus is rendered avirulent, implying an inability to induce lipoic acid-independent metabolic programs to promote survival. Together, our results define the major pathways of lipoic acid biosynthesis and salvage in S. aureus and support the notion that bacterial nutrient acquisition schemes are instrumental in dictating pathogen proclivity for an infectious niche.